2022
DOI: 10.5334/jopd.58
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Individual Differences in Response to Reading Intervention: Data from Project KIDS (Kids and Individual Differences in Schools)

Abstract: This manuscript provides information on datasets pertaining to Project KIDS. Datasets include behavioral and achievement data for over 4,000 students between five and twelve years old participating in nine randomized control trials of reading instruction and intervention between 2005-2011, and information on home environments of a subset of 442 students collected via parent survey in 2013. All data is currently stored on an online data repository and freely available. Data might be of interest to researchers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Substantive knowledge about how the model (and its assumptions) aligns to the data and theory would help distinguish well-fitting but theoretically inconsistent models. This finding was further illustrated in an applied example using publicly available longitudinal data (i.e., Project KIDS database; van Dijk et al, 2022). Specifically, our applied example demonstrated that the same dataset could be analyzed through multiple distinct longitudinal SEM approaches and produce similarly well-fitting models according to their fit statistics.…”
Section: Intentionality In Analytic Approachmentioning
confidence: 58%
See 1 more Smart Citation
“…Substantive knowledge about how the model (and its assumptions) aligns to the data and theory would help distinguish well-fitting but theoretically inconsistent models. This finding was further illustrated in an applied example using publicly available longitudinal data (i.e., Project KIDS database; van Dijk et al, 2022). Specifically, our applied example demonstrated that the same dataset could be analyzed through multiple distinct longitudinal SEM approaches and produce similarly well-fitting models according to their fit statistics.…”
Section: Intentionality In Analytic Approachmentioning
confidence: 58%
“…Data for the current applied example come from the Project KIDS database (van Dijk et al, 2022), which is an open-source dataset available on the data repository LDbase (ldbase.org).…”
Section: Datamentioning
confidence: 99%
“…This becomes a direct citation for any future publications using that data. For a recent example of publishing about the methods of a study in learning disabilities research, see van Dijk et al (2022). Considering code sharing, these can be uploaded in the same manner as other supplemental materials or can be hosted on code-specific websites (e.g., GitHub).…”
Section: Resourcesmentioning
confidence: 99%
“…IDA involves combining multiple datasets to create a new analytic dataset that maintains variability at the item-or individual-level, which allows for future analyses that may advance knowledge of what works, for whom, and under what conditions (e.g.,van Dijk et al, 2022).The last two quality indicators refer to the documentation that accompanies a shared database: Documentation of study design and purpose, and documentation of variable names and values. These materials are necessary components to understanding and interpreting the data.Logan and colleagues (2021) present an in-depth discussion of data sharing for education research including common concerns, refutations, and resources.…”
mentioning
confidence: 99%
“…Data from this study come from a randomized trial of a reading intervention program (Individualizing Student Intervention [ISI]; Connor et al, 2013). The data are part of the open data set Project KIDS (see van Dijk et al, 2022). We use data from Study 9 of Project KIDS.…”
Section: Participantsmentioning
confidence: 99%